2019
DOI: 10.4236/msa.2019.103014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluorine and Silicon Incorporation on Tribological Performance of Diamond-Like Carbon Films

Abstract: Diamond-like carbon (DLC) is a metastable amorphous film that exhibits unique properties. However, a number of limitations exist regarding the use of DLC, for instance, its tribological characteristics. In this article, the fluorine and silicon incorporated diamond-like carbon (F-DLC and Si-DLC) films are studied, taking into account the tribological properties of these films compared with pure DLC. The structures of the films were characterized using Auger electron spectroscopy and Raman spectroscopy. The har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The previous study reported that DLC, Si-DLC, and F-DLC films' friction coefficients were 0.18, 0.03, and 0.16, respectively (Jongwannasiri et al, 2019b). The decreasing friction coefficient of the F-DLC film was due to the formation of repulsive forces with F atoms.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The previous study reported that DLC, Si-DLC, and F-DLC films' friction coefficients were 0.18, 0.03, and 0.16, respectively (Jongwannasiri et al, 2019b). The decreasing friction coefficient of the F-DLC film was due to the formation of repulsive forces with F atoms.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, three types of DLC coating, namely DLC, Si-DLC, and F-DLC, were deposited on OMIs. A previous study showed that the Si-DLC and F-DLC films deposited at a gas flow rate ratio of 2:1 had shown the lower friction coefficients among all the compositions of DLCs (Jongwannasiri et al, 2019b). Consequently, both of them were selected to study in this experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also hinted at the possibility of an improvement in the toughness properties due to the formation of a Si-rich transfer layer on the surface. 66,67 However, the thick SiO x transfer layer obtained at high laser annealing energy densities leads to a film showing high wear. This result indicates that Si-DLC thin films are unsuitable for applications involving high-energy UV irradiation.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
“…In their calculations, the lowest friction was obtained from the F-terminated DLC model, indicating that a stronger repulsive force and weaker van der Waals interaction occurred at the sliding surface of the F-terminated DLC model. Furthermore, some studies have shown that a-C:H:F films exhibit lower friction coefficients than a-C:H films in ambient air. …”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the tribological properties of a-C:H:F and a-C:F films, and several theories regarding the role of F atoms on friction surfaces have been proposed. Among them, two main reasons for the low friction coefficient of a-C:F films are the passivation of the dangling bonds by F and the repulsive force occurring at the sliding interface owing to the high electronegativity of F .…”
Section: Introductionmentioning
confidence: 99%